Spectrum of BCR-ABL mutations in Azerbaijanian imatinib-resistant patients with chronic myeloid leukemia - Aypara Hasanova; Chingiz Asadov; Nigar Karimova; Aytan Shirinova; Gunay Aliyeva; Zohra Alimirzoyeva (Frontiers Media S.A., 2023)
Objective: BCR-ABL1 kinase domain (KD) mutations can lead to resistance to first- and second-generation tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML). Here, we present the first report of the spectrum of mutations in the BCR-ABL1 KD of CML patients from Azerbaijan.Materials and methods: Samples for mutation screening were obtained from patients experiencing resistance to first line TKIs or from patients in acceleration phase (AP) or blast crisis (BC) at the time of diagnosis. The cDNA region corresponding to BCR-ABL1 KD was sequenced by pyrosequencing method. The χ2 test was used to assess the association of categorical variables between mutation-positive and -negative groups. In addition, the Kaplan-Meier method was applied to generate survival curves.Results: Eight different point mutations were identified in 22 (13.4%) out of 163 CML patients experiencing resistance to TKIs. The types of mutations detected were as follows: Contact binding site mutations 50% (11), SH2 domain mutations 27.4% (six), P-loop mutations 18.1% (four), and SH3 domain mutations accounting for 4.5% (one). The most common mutation was T315I, accounting for 5% (n = 8) of all patients. Significant association was identified between BCR-ABL1 mutations and additional chromosomal aberrations as well as between the mutations and disease phases (p < 0.05). Twelve out of 22 patients with BCR-ABL1 mutations and seven out of eight with T315I were in BC. Overall survival (OS) of the patients with BCR-ABL1 mutations was significantly lower comparing to the patients with no mutation (p < 0.05) and 8 patients with T315I mutation presented OS of 0%.Conclusion: T315I was the most commonly identified BCR-ABL1 mutation in TKI-resistant CML patients of Azerbaijani origin, being associated with disease progression and poor OS.